Analysis of BPJS Kesehatan Patient Satisfaction with Health Services in Region General Hospital dr.Soegiri, in Lamongan District - Chaidir Annas; Badri Munir Sukoco (Airlangga Development Journal, 2026)
Business competition in the field of services has experienced a significant increase nowadays, especially in healthcare services. The government is one of the agencies obligated to fulfill the needs of the community in public services. One of the healthcare service providers is dr. Soegiri Regional General Hospital, a Type B regional hospital in Lamongan Regency. Conducting evaluation and measurement of the provided healthcare services is essential. By utilizing the SERVQUAL method, we will examine the quality of healthcare services provided by dr. Soegiri Regional General Hospital through five service dimensions. In this research, we utilized primary data obtained from patients of dr. Soegiri Regional General Hospital. The findings indicate variations in patient satisfaction levels based on educational background, duration of visit, and BPJS (Healthcare and Social Security Agency) coverage.